2013
DOI: 10.4236/ss.2013.42032
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evaluation of TruFUSE® Lumbar Facet Fusion System

Abstract: Introduction: The TruFUSE ® lumbar facet fusion system is a unique allograft milled bone dowel used to fuse facet joints. We evaluated subjects undergoing TruFUSE ® fusion for stable grade I spondylolisthesis and stenosis comparing operative time, length of stay, blood loss and outcome to a similar literature-based cohort of patients undergoing pedicle screw fusion (PSF). Methods: From 2009 to 2011, 41 subjects (17 M, 24 F, aver. age 69.5 yr) underwent TruFUSE ® facet fusion along with transverse process bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Targeting the facets as the only fusion site has been proposed using a dedicated interfacetary grafting material. Marron et al demonstrated the successful implementation of an allograft milled bone dowel facet fusion system to augment laminectomy and transverse process fusion procedures for the treatment of stable Grade I degenerative spondylolisthesis in a cohort of 41 patients [12]. They demonstrated that 95% of the patients had spinal stability at an average of six months post-operatively and 100% had signs of early fusion [12].…”
Section: Discussionmentioning
confidence: 99%
“…Targeting the facets as the only fusion site has been proposed using a dedicated interfacetary grafting material. Marron et al demonstrated the successful implementation of an allograft milled bone dowel facet fusion system to augment laminectomy and transverse process fusion procedures for the treatment of stable Grade I degenerative spondylolisthesis in a cohort of 41 patients [12]. They demonstrated that 95% of the patients had spinal stability at an average of six months post-operatively and 100% had signs of early fusion [12].…”
Section: Discussionmentioning
confidence: 99%
“…The subjective evaluation was conducted through the Kujala Anterior Knee Pain Scale [ 21 ], the Lysholm Knee Score and the Tegner Activity Score [ 22 ]. Furthermore, patients were asked to subjectively evaluate the outcome of the operation according to the following options (subjective evaluation score): 5—excellent; 4—somewhat improved; 3—unchanged; 2—somewhat worse; 1—significantly worse [ 23 ], and asked if they would have the operation again. Lastly, isokinetic knee flexor and extensor strength tests were performed at 60°/s using an isokinetic dynamometer (Biodex System 4 Pro: Biodex Medical Systems, Shirley, NY, USA).…”
Section: Inclusion/indications Of the Lateral Trochlear Lengthening Osteotomymentioning
confidence: 99%
“…Благодаря меньшей травматичности хирургического вмешательства, низкой интраоперационной кровопотере, а также сокращению длительности реабилитации пациентов эти технологии выглядят В настоящее время опубликованы результаты исследований, в которых изучались альтернативные варианты фиксации ПДС с применением имплантатов, не только стабилизирующих сегмент, но и создающих условия для формирования заднего костного блока. Наиболее близкие к разработанной нами технологии методы межсуставной фиксации рассматриваются либо как вариант лечения изолированного поражения дугоотростчатых суставов, либо в комбинации с межтеловым спондилодезом, однако перкутанная транспедикулярная фиксация в них не включена [17,21,22]. Кроме того, данные технологии подразумевают применение открытого или полуоткрытого доступа к дугоотростчатому суставу для установки имплантата.…”
Section: Russian Journal Of Neurosurgeryunclassified